Archiwum Andrzeja Wajdy - Matysiak, Mateusz (Przestrzenie Teorii, 2017)
The author offers a concise description of the contents of the Andrzej Wajda Archive, which is located in the Manggha Museum of Japanese Art and Technology in Kraków. His enormous legacy comprises not just his film and theatre work, but the whole of the director's exceptionally colourful and intensive creative, political and social activity.